Proceedings of the 2nd Southeast Asian Academic Forum on Sustainable Development (SEA-AFSID 2018) 2021
DOI: 10.2991/aebmr.k.210305.031
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Sustainability in Radio Broadcasting Towards a Media Convergence Era by Marketing Public Relations Activities to Create Awareness of Prambors Radio in Indonesia

Abstract: This research aims to examine the challenges of sustainability in radio broadcasting of Prambors radio toward media convergence by marketing communication activities to create awareness. The research uses a case study method. The data was obtained through open interviews, non-participant observations, and public documentation such as the company profile, the company website, and social media. The data analysis used a coding concept consisting of open coding, axial coding, and selective coding. The research res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Moreover, it is important to note that public relations sometimes play a More important role to develop awareness regarding products or services. Past studies have revealed that public relations campaigns have a positive effect on the behavior of the customer and the development of loyalty through brand awareness (Sari, Irawan, Mone, & Aras, 2021). It was revealed by the scholars that brand awareness of the McAfee products was positively affected by the PR activities of the firm in Indonesia.…”
Section: Public Relations and Brand Awarenessmentioning
confidence: 99%
“…Moreover, it is important to note that public relations sometimes play a More important role to develop awareness regarding products or services. Past studies have revealed that public relations campaigns have a positive effect on the behavior of the customer and the development of loyalty through brand awareness (Sari, Irawan, Mone, & Aras, 2021). It was revealed by the scholars that brand awareness of the McAfee products was positively affected by the PR activities of the firm in Indonesia.…”
Section: Public Relations and Brand Awarenessmentioning
confidence: 99%
“…Traditional media consumption is robust and widespread and remains the most potent source of information, learning and entertainment. Even as new mass media appeared and reduced its market share, the medium that has evolved is now finding rebirth on digital platforms such as internet radio (Sari et al, 2021). Since the birth of the internet, a new type of media has evolved, and websites, apps, and social media are new ways for individuals to communicate with each other and with vast audiences (Ferguson & Greer, 2018;Silva et al, 2018).…”
Section: Media Transitions (Exposure) and Reportingmentioning
confidence: 99%
“…Exploring the high-quality development of the media industry from the perspective of deep media integration requires rigorous qualitative analysis and quantitative scientific research [ 12 ]. However, from a practical standpoint, China's media integration development strategy is still in the exploration stage, and the matching mechanism for the media industry to develop to the high-quality stage is not yet mature.…”
Section: Introductionmentioning
confidence: 99%